ANALISIS STRATEGI BRAND PIT A PAT DALAM MEMBANGUN KEPERCAYAAN KONSUMEN DI MEDIA SOSIAL TWITTER - Putri Nabilah Fide; Bayu Pratama Wiratsongko (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to identify and analyze the strategies used by the PIT A PAT brand in building consumer trust on Twitter social media. Consumer trust is crucial in online transactions because of the vulnerability of cyber crime. Therefore, it is necessary for companies to create and develop strategies to increase consumer trust, especially brands that use social media as a medium of buying and selling. The reason is that there are three factors that can shape consumer trust, namely ability, benevolence, and integrity of the company as a seller. This study uses a descriptive qualitative method based on the postpositivism paradigm. The research findings show that the strategy adopted by the PIT A PAT brand in building consumer trust is considered effective and successful, as seen from Twitter analytical data. The strategies carried out include marketing that displays the best design catalogs, creating credible account profiles, communicating with consumers intensely, and running a business with integrity. Twitter. Consumer trust is crucial in online transactions because of the vulnerability of cyber crime. Therefore, it is necessary for companies to create and develop strategies to increase consumer trust, especially brands that use social media as a medium of buying and selling. The reason is that there are three factors that can shape consumer trust, namely ability, benevolence, and integrity of the company as a seller. This study uses a descriptive qualitative method based on the postpositivism paradigm. The research findings show that the strategy adopted by the PIT A PAT brand in building consumer trust is considered effective and successful, as seen from Twitter analytical data. The strategies carried out include marketing that displays the best design catalog, creating a credible account profile, communicating with consumers intensely, and conducting business with integrity and professionalism.